Wonderful Ecosystems - Spilsbury, Louise (Oxford University Press, 2010)
Read and discover all about wonderful ecosystems on Earth ... How are polar bears adapted to living in a frozen ecosystem? What are decomposers? This exciting new series of non-fiction readers provides interesting and educational content, with activities and project work. The readers are graded at four levels, from 3 to 6, suitable for students from age 8 and older